Penyuluhan Bahaya Narkotika dan Psikotropika di Kalangan Siswa SMAN 05 Tinggi Moncong, Gowa, Sulawesi selatan - Sitti Faika; Ramdani Ramdani; Nita Magfirah Ilyas (INOVASI: Jurnal Hasil Pengabdian Masyarakat, 2021)
Abstract. Starting from 2018 until 2019, the study investigates the prevalence of drug abuse in Indonesia increasing gradually from 24% in 2018 to 28% in 2019. National Narcotics Agency reported that for nearly two years, Makassar has ranked 9th for drug abuse among adolescents and most of them are students. According to Tribun Makassar, more than 1.500 patients are hospitalized due to drug abuse. The Importance of health education for fighting drug abuse in student's majorities in high school is the aim of this PKM. Due to the students are the target of drug delivery, then educating high school students related the drug abuse, the effect of consumed the drugs, and how to avoid drug abuse is the priority of this activity. hopefully, this PKM will reduce the level of abuse of narcotic drugs among high school levels. Keywords: Drug Abuse, Adolescents, Health Education